Factors associated with self-determined motivation in young basketball athletes: A systematic review - dos Santos Goes Q. (2021)
© 2021 Sociedad Revista de Psicologia del Deporte. All rights reserved.The present study aimed to analyze the psychological and psychosocial factors associated with self-determined motivation of young basketball athletes through a systematic review. After search, 377 articles were identified from a systematic approach following the PRISMA statement via electronic databases (Web of Science, PubMed, Science Direct, SportDiscus, Psylnfo, Scopus, and Scielo). Only original peer-review articles published in the English, Spanish or Portuguese language focusing in young basketball athletes and investigated self-determined motivation were included. Fourteen studies were included in the qualitative synthesis. These studies investigated 3,396 young basketball athletes and 37 psychological and psychosocial factors associated with their self-determined motivation. The most used instrument to analyze the self-determined motivation of young basketball athletes were the Intrinsic Motivation Scale and Sports Motivation Scale. It was concluded that a coach motivational climate and basic psychological needs (BPNs) were the main psychosocial and psychological antecedents, respectively, associated with young basketball athletes' self-determined motivation, whereas increased effort in training was the main consequence associated with self-determined motivation.